2014
DOI: 10.1007/s00401-014-1287-x
|View full text |Cite
|
Sign up to set email alerts
|

Focusing the amyloid cascade hypothesis on N-truncated Abeta peptides as drug targets against Alzheimer’s disease

Abstract: Although N-truncated Aβ variants are known to be the main constituent of amyloid plaques in the brains of patients with Alzheimer’s disease, their potential as targets for pharmacological intervention has only recently been investigated. In the last few years, the Alzheimer field has experienced a paradigm shift with the ever increasing understanding that targeting amyloid plaques has not led to a successful immunotherapy. On the other hand, there can be no doubt that the amyloid cascade hypothesis is central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 111 publications
(153 reference statements)
3
140
0
Order By: Relevance
“…Besides full-length Aß peptides, a variety of different N-truncated Ab peptides have been identified within the cored and diffuse amyloid plaques in the AD brain starting with amino residue Ala-2, pyroglutamylated Glu-3, Phe-4, Arg-5, His-6, Asp-7, Ser-8, Gly-9, Tyr-10, and pyroglutamylated Glu-11 (Antonios et al, 2013;Bayer and Wirths, 2014;Lemere et al, 1996;Saido et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Besides full-length Aß peptides, a variety of different N-truncated Ab peptides have been identified within the cored and diffuse amyloid plaques in the AD brain starting with amino residue Ala-2, pyroglutamylated Glu-3, Phe-4, Arg-5, His-6, Asp-7, Ser-8, Gly-9, Tyr-10, and pyroglutamylated Glu-11 (Antonios et al, 2013;Bayer and Wirths, 2014;Lemere et al, 1996;Saido et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a series of studies on human CSF has identified numerous APP N-terminal fragments (29) and N-terminally extended A␤ species that may have (patho)physiological functions (44,45). Evidence also exists for the N-terminal truncation of the A␤ peptide at every one of its first 11 amino acids, although again, the biological relevance of the majority of these species remains uncertain (46). At least one N-terminally truncated species of A␤ (A␤5-X) has been shown to increase in the CSF of patients treated with a BACE1 inhibitor, suggesting that it is liberated in a BACE1-independent manner and that the protease responsible for its liberation acts in direct competition with BACE1 (47).…”
Section: Mystery Proteasesmentioning
confidence: 99%
“…Nevertheless, according to the amyloid cascade hypothesis first proposed in the 1990s, [6] the imbalance between production and clearance of the A peptides is the origin of the accumulation of peptides that further leads to the aggregation of the soluble monomeric peptide into fibrils and amorphous aggregates detected in the senile plaque. [3][4][5][6][7][8][9] The amyloid cascade is an early event and plays a causal role in AD (Scheme 1). The complete aggregation pathway from the monomeric peptide to the fibrils contains several steps including oligomers, protofibrils, and fi-etiology of the disease.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…[9,[24][25][26] The reason for such heterogeneity is unclear. In seminal reports by Masters and co-workers, [27,28] the quantity of A 4-n was found to be predominant in the amyloid deposits of AD patients.…”
Section: N-terminally Truncated Peptidesmentioning
confidence: 99%